Development of a Z39.50 server prototype for the University of the Philippines Library System - Gamara, Ivan Cedric B.; Angeles, Chito N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman x, 77 leaves, 2009)
A Z39.50 server prototype has been successfully developed for the University of the Philippines Diliman library system. The prototype currently can import bibliographic records in MARC format from the UP iLib system. It then indexes the records using an existing technology called Zebra. The records are made available through a web service in which a Z39.50 client software can connect to.
The Z-server prototype can be accessed by any Z39.50 client software as long the port that the prototype uses is not blocked. The search fields of the UP iLib OPAC module has been incorporated as the search attributes for the prototype. It uses the Bib1 profile which is mapped to MARC21 fields and subfields.
The study has been conducted using an iterative approach. The requirements for the prototype were obtained in a short period of time. The model and the prototype itself were constructed in likely the same amount of time. The models and the prototype itself were constructed in likely the same amount of time. After each iterative cycle, the prototype is tested and validated by UP iLib system administrator. This was done until the prototype has been deemed acceptable and has satisfied the requirements that has been defined.
The Z-server prototype has been turned over to the UP iLib system administrator. It will likely be implemented alongside the UP iLib system in the future.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Rapid prototyping; Z39.50 (Standard)